Assessment of dynamic microbial community structure and rhizosphere interactions during bioaugmented phytoremediation of petroleum contaminated soil by a newly designed rhizobox system - Yang K.M. (2023)
To understand the plant (Vigna unguiculata) and plant-growth promoting bacteria (PGPB) (Microcococcus luteus WN01) interactions in crude oil contaminated soil, experiments were conducted based on the newly designed rhizobox system. The rhizobox was divided into three main compartments namely the rhizosphere zone, the mid-zone, and the bulk soil zone, in accordance with the distance from the plant. Plants were grown in these three-chambered pots for 30 days under natural conditions. The plant root exudates were determined by analyzing for carbohydrates, amino acids, and phenolic compounds. The degradation of alkane, polycyclic aromatic hydrocarbons (PAHs), and total petroleum hydrocarbons (TPHs) were quantified by GC-FID. Soil catalase, dehydrogenase, and invertase activities were determined. The microbial community structure was assessed using denaturing gradient gel electrophoresis (DGGE). Results showed that the inoculation of M. luteus WN01 significantly enhanced cowpea root biomass and exudates, especially the phenolic compounds. Bioaugmented phytoremediation by cowpea and M. luteus promoted rhizodegradation of TPH. Cowpea stimulated microbial growth, soil dehydrogenase, and invertase activities and enhanced bacterial community diversity in oil contaminated soil. The rhizosphere zone of cowpea inoculated with M. luteus showed the highest removal efficiency, microbial activities, microbial population, and bacterial community diversity indicating the strong synergic interactions between M. luteus and cowpea.